Ответы и объяснения

  • Voxman
  • главный мозг
2013-05-31T10:59:10+00:00

 

y = log_3(11 + 4x - x^2) - 2\\\\ (f(g(x)))' = \frac{dg(x)}{dx}\frac{df(g(x))}{dg(x)} = g'(x)\frac{df(g(x))}{dg(x)}\\\\ y' = (4 - 2x) \frac{1}{(11 + 4x - x^2)ln(3)}\\\\ (4 - 2x) \frac{1}{(11 + 4x - x^2)ln(3)} = 0,\\\\ 11 + 4x - x^2 \ne 0,\\\\ 4 - 2x = 0, -2x = -4, \ \underline{x = 2}\\\\ 11 + 4x - x^2 = 0, \\\\\ D = 16 + 44 = 60\\\\ x_1 = -\frac{-4 - \sqrt{60}}{2} = 2 + \sqrt{15}\\\\ x_2 = -\frac{-4 + \sqrt{60}}{2} = 2 - \sqrt{15}

 

Методом интервалов находим, что y' > 0:

 

x \in (2 - \sqrt{15}; 2) \cup (2 + \sqrt{15}; +\infty)

 

тогда x = 2 - точка максимума.

 

 

\max\limits_{x} y = y(2) = log_3(11 + 8 - 4) - log_39 = log_3\frac{15}{9} = log_3\frac{5}{3}